IMPLEMENTING READING TO LEARN (R2L) TO SCAFFOLD THE TEACHING OF WRITING ANALYTICAL EXPOSITION TEXT FOR DISADVANTAGED STUDENTS - Hasna Parida, - (2019)
One of the mandated basic competencies for vocational high school is to write analytical exposition text. It has been observed that many students with disadvantaged background have difficulties in coping with the competencies due to limited access to linguistic and academic resources. These disadvantaged students are less prepared to write academically valued texts. Rapid growth of research about Reading to Learn and scaffolding in international contexts show promising results that this approach could accelerate disadvantaged students' literacy development. This study is aimed at figuring out how the implementation of R2L can scaffold the mandated basic competencies for disadvantaged students and how they improve students' writing competency. The data were gained from six focal students at a vocational high school through qualitative case study design. The analysis shows that Reading to Learn in the context of this study shows its affordability in scaffolding the teaching of writing analytical exposition text on macro and micro skills and improved students competency depicted from the 14 R2L's descriptors. The analysis shows some challenges and opportunities for future research direction in Indonesian contexts.; Salah satu kompetensi dasar yang diamanatkan untuk sekolah menengah kejuruan adalah untuk menulis teks eksposisi analitis. Berdasarkan hasil pengamatan, banyak siswa dengan latar belakang yang kurang beruntung memiliki kesulitan untuk mencapai kompetensi yang ada karena terbatasnya akses terhadap literatur akademik dan kebahasaan. Siswa yang kurang beruntung ini kurang siap untuk menulis teks akademis. Penelitian tentang Reading to Learn dan scaffolding dalam konteks internasional menunjukkan hasil yang menjanjikan bahwa pendekatan ini dapat mempercepat perkembangan literasi siswa yang kurang beruntung ini. Penelitian ini bertujuan untuk mengetahui bagaimana implementasi R2L dapat membantu pengajaran kompetensi dasar yang diamanatkan ini, terutama bagi para siswa yang kurang beruntung dan bagaimana pendekatan ini dapat meningkatkan kompetensi menulis siswa. Data diperoleh dari enam siswa fokus di sekolah menengah kejuruan melalui desain penelitian kualitatif khusunya studi kasus. Hasil analisis menunjukkan bahwa R2L dalam konteks penelitian ini mampu membantu pengajaran menulis teks eksposisi analitis pada keterampilan makro dan mikro dan menigkatkan kompetensi siswa yang digambarkan melalui 14 deskriptor dari R2L. Analisis dalam penelitian ini menunjukkan beberapa tantangan dan peluang untuk arah penelitian di masa yang akan datang terutama dalam konteks Indonesia.